Enhancement of luminous flux and color quality of white light-emitting diodes by using green (Y,Gd)BO3:Tb3+ phosphor - My Hanh Nguyen Thi; Phung Ton That; Nguyen Doan Quoc Anh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
In the study, we analyzed and clarified the effect of green (Y,Gd)BO3:Tb3+ phosphor on chromatic homogeneity and optical performance of multi-chip white LEDs (MCW-LED). Thereby there is a solution to get the best luminous efficiency. In addition, (Y,Gd)BO3:Tb3+ is known as one of the factors that has a significant impact on lighting performance, so it needs to add the (Y,Gd)BO3:Tb3+ phosphor in the structure of LEDs to combine with the yellow phosphor YAG:Ce3+ to receive the best results. Therefore, the concentration and size of (Y,Gd)BO3:Tb3+ should be choose carefully so that the presentation of MCW-LEDs would be more incredible. The results show that when the concentration of green-emitting (Y,Gd)BO3:Tb3+ phosphor tends to increase, it also helps the color homogeneity and the lumen efficiency of MCW-LEDs with the average correlated color temperature (CCT) of 5600 K-8500 K become better.